Transauricular vagus nerve stimulation in preventing post-traumatic stress disorder in emergency trauma surgery patients in China: a study protocol for a multicenter, double-blind, randomised, controlled trial - Jun Zhang; Xin Yu; Gang Chen; Yu Li; Qi-Hong Shen; Xinru Lin; Tieshuai Liu; Yunyun Yu; Jingwen Liang (BMJ Open)
Introduction The incidence of post-traumatic stress disorder (PTSD) in emergency trauma surgery patients is 24%, emphasising the urgent need for effective early interventions and treatments. Transauricular vagus nerve stimulation (ta-VNS) modulates the autonomic nervous system by stimulating the nucleus tractus solitarius while affecting PTSD-related neural networks, including the prefrontal cortex, hippocampus and amygdala, potentially offering new options for PTSD prevention and treatment. This study aims to evaluate the efficacy and safety of ta-VNS in preventing PTSD in emergency trauma surgery patients.Methods and analysis This multicentre, double-blind, randomised controlled study aims to evaluate the incidence of PTSD in emergency trauma surgery patients receiving either ta-VNS or sham stimulation. A total of 350 participants will be randomly assigned to receive either active or sham stimulation. The active group will undergo electrical stimulation of the left cymba conchae at 30 Hz with a pulse width of 250 µs, using a 30 s on/30 s off cycle. The intensity will start at 0.4 V, increasing in 0.4 V increments until a tingling sensation is detected, and will be adjusted to the highest tolerable level without causing pain. The initial intervention will begin once informed consent is obtained and randomisation is completed in the preoperative preparation room, continuing until the surgery is finished. For the four postoperative days, the intervention will be administered two times per day in 2-h sessions each morning and evening. The sham stimulation group will follow a similar procedure without actual stimulation. The primary outcome is the incidence of PTSD evaluated on postoperative day 30, with secondary outcomes including recovery quality, sleep quality, and adverse events.Ethics and dissemination The protocol received approval from Sir Run Run Shaw Hospital, affiliated with Zhejiang University School of Medicine, on 15 October 2024 (approval number: 20240562). The study will adhere to the Declaration of Helsinki guidelines, and written informed consent will be obtained from all participants. Results will be submitted to a peer-reviewed journal for publication.Trial registration number China Clinical Trial Registration Center (ChiCTR2400080342). Trial details: https://www.chictr.org.cn/showproj.html?proj=217809